A Journal’s Hormonal Balance - Paz-Pacheco, Elizabeth (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Let us consider that this generation of JAFES is in adolescence: we must help it maintain a balance of hormones that, over time, affect the Journal’s many processes, including mood, growth, development, metabolism and reproduction. The Journal needs to function well through its organs and systems: foremost, our readers including health care professionals and their patients; equally, our authors and their institutions; and finally, our member Societies.